1995
DOI: 10.1002/bit.260480613
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic approach to explain cell adhesion to air–medium interfaces

Abstract: Cell damage has been observed in suspension cell cultures with air sparging, especially in the absence of any protective additives. This damage is associated with cells adhering to bubbles, and it has been shown that if this adhesion is prevented, cell damage is prevented. This article presents a thermodynamic approach for predicting cell adhesion at the air-medium interface. With this relationship it can be shown that cell-gas adhesion can be prevented by lowering the surface tension of the liquid growth medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
(15 reference statements)
2
16
0
Order By: Relevance
“…5). As previously reported (Chattopadhyay et al, 1995a;Dey and Emery, 1999) 1.0 g/L PF-68 can rapidly decrease the surface tension from 72 dyn/cm to around 55 dyn/cm within 0.1 s, followed by a slow decrease to the equilibrium surface tension reported by Chattopadhyay et al (1995b) to be 45 dyn/cm, as determined by the Wilhelmy plate method. In contrast, OM, NM, and CM4 rapidly (less than 0.1 s) lowered the surface tension with very little change after the initial drop, while 0.28 g/L DM took the longest, approximately 0.5 s, to achieve its equilibrium value.…”
Section: Dynamic Surface Tensionsupporting
confidence: 51%
See 1 more Smart Citation
“…5). As previously reported (Chattopadhyay et al, 1995a;Dey and Emery, 1999) 1.0 g/L PF-68 can rapidly decrease the surface tension from 72 dyn/cm to around 55 dyn/cm within 0.1 s, followed by a slow decrease to the equilibrium surface tension reported by Chattopadhyay et al (1995b) to be 45 dyn/cm, as determined by the Wilhelmy plate method. In contrast, OM, NM, and CM4 rapidly (less than 0.1 s) lowered the surface tension with very little change after the initial drop, while 0.28 g/L DM took the longest, approximately 0.5 s, to achieve its equilibrium value.…”
Section: Dynamic Surface Tensionsupporting
confidence: 51%
“…Even though a number of protective mechanisms of PF-68 have been proposed (Chisti, 2000;Wu, 1995), the ability of PF-68 to inhibit cell-bubble attachment is considered the primary mechanism. Chattopadhyay et al (1995b) suggested that this inhibition of cell-interface adhesion is the result of PF-68 significantly decreasing the surface tension of the gas-liquid interface such that adhesion to the gas-liquid interface is thermodynamically unfavorable. The interaction of nonionic block copolymers (such as PF-68) with air-water interfaces is a significant subset area of research in the general area of surfactants, air-water interface interactions.…”
Section: Introductionmentioning
confidence: 98%
“…Cell damage could be suppressed by adding a small amount ( ‡0.02% by wt) of carboxy methyl cellulose to the culture medium [45]. Methyl cellulose additives have been associated with the reduced attachment of cells to bubbles [46][47][48][49].…”
Section: Resultsmentioning
confidence: 99%
“…Given that the driving force of the bubble rupture process is a pressure difference, lowering the surface tension lowers the driving force which lowers the overall EDR associated with the bubble rupture. Lowering the surface tension of the gas-liquid interface also makes the attachment of cells to gas-medium interfaces thermodynamically unfavorable (Chattopadhyay et al 1995b). Michaels et al (1995) reported that PF-68 can significantly increase the induction time required before a cell-to-bubble attachment can occur to 5-20 s. This led Meier et al (1999) to create a mathematical model simulating the process of cells following streamline flows around a sphere to investigate the role of cell-to-bubble attachment in the total bubble-associated cell damage and reconcile some contradictory observations in the literature.…”
Section: Cell Damage From Spargingmentioning
confidence: 98%